A contingency approach to representative bureaucracy: power, equal opportunities and diversity - Groeneveld, Sandra; Walle, Steven Van de (2010)
In this article we develop a contingency approach to representative bureaucracy. We argue that representative bureaucracy is a multidimensional and changing concept, and that in the academic and policy debate on representative bureaucracy three different dimensions are intermingled: power, equal opportunities and diversity. These dimensions not only reflect a particular view on the role of the state and the relation between the state and citizens, they also diverge in the motives for making the bureaucracy representative. Even the conception of what representation means can be totally different. We conclude that modern diversity management approaches alone may not contribute to nation-building because these mainly emphasize organizational performance. Approaches to representative bureaucracy in nation-building must also be built on moral arguments and underline the exemplary role of the state. In addition, the political viability of managerial and moral approaches needs to be taken into account through acknowledging political realities and existing distributions of power in society. - Reproduced.
Keywords: Bureaucracy